Two new heterobathmiid moth species with distinctive female genital configurations (Lepidoptera: Heterobathmiidae) - Hünefeld, Frank; Kristensen, Niels P. (Zootaxa, 2012)
Two new species of the basal (non-glossatan) moth family Heterobathmiidae are described: Heterobathmia megadecellaand H. nielsenella. Both species have particularly notable features in their female postabdomen: H. megadecella has adistinct sclerotization in the genital chamber and a somewhat elaborate sclerite complement on the otherwise membranousventer of the ‘terminal unit’ formed by segments IX–X(XI), and H. nielsenella has a remarkable forwards extension of thesclerotized upper surface of the ‘subgenital plate’ and a continuation of this extension into a sizable apodemal lamella.The description of these taxa in advance of a comprehensive taxonomic treatment of all presently available Heterobathmia(including a number of additional undescribed species) is prompted by the need for available names to be used in a morphological treatment of the heterobathmiid postabdomen now nearing completion.